Religion and Voting on Abortion Reform: A Follow-up Study - Richardson, James T. (Journal for the scientific study of religion, 1975)
The research relates four independent variables to the voting behavior of legislators in a western state on the question of abortion reform during three sessions of the state legialature. The four variables include religious affiliation, party, age, and rural-urban constituency. Special attention is given to religious affiliation because of the assumed saliency of abortion reform for certain religious groups. The state chosen for study has large groups of Catholics and Mormons, both of which are opposed to abortion reform on theological grounds. Results indicate that religious affiliation was a better predictor of legislative voting on abortion reform than any of the other variables.